La presse arabophone en Angleterre au prisme des politiques du Golfe - Amal Nader; Mohamed Bendahan (Revue des Mondes Musulmans et de la Méditerranée)
In the context of this article, we choose to study three Arab newspapers, published in London, which have survived the changes in the profession of the press by knowing how to evolve towards online practices. They bring together Arabic-speaking journalists from different Arab countries. These Arabic-language daily newspapers covered and accompanied major world events as well as current affairs in the Arab world by following distinct editorial policies, each supporting one of the Gulf countries through a historic conflict that developed between 2017 and 2021 and led to diplomatic rupture and the closing of borders. The following newspapers were studied: Acharq Alawsat or The Middle East, a Saudi newspaper; Alquds Alarabi or Arab Jerusalem, currently pro-Qatari; Alarab or The Arabs, currently pro-Emirati. The purpose of the approach is to answer a question of no little significance: what place does this Arabic-speaking press occupy, between managing its integrated presence in a host country and a mission related to its region of origin? In other words: does this press see itself as a fully Arab press or rather as a press in exile?